2020
DOI: 10.1021/acs.oprd.0c00240
|View full text |Cite
|
Sign up to set email alerts
|

Digital Design of Batch Cooling Crystallization Processes: Computational Fluid Dynamics Methodology for Modeling Free-Surface Hydrodynamics in Agitated Crystallizers

Abstract: A framework for the digital design of batch cooling crystallization processes is presented comprising three stages, which are based on different levels of process complexity, integrating crystallizer hydrodynamics with crystallization kinetics and consequently with expected crystal size distribution. In the first stage of the framework, a computational fluid dynamics methodology is developed to accurately assess hydrodynamics in a typical batch crystallizer configuration, comprising a 20 L scale dish-bottom ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Szilaǵyi and Nagy 25 showed how parallel GPUs running a high-resolution finite volume technique improved calculation speed significantly, enough for real-time resolution of a multidimensional PBM. Camacho Corzo et al 26 used computational fluid dynamics (CFD) to investigate the hydrodynamics inside a batch crystallizer, suggesting that these simulations could be paired with a morphological PBM to create a more robust representation of the process. 27 Another recent advancement for MPC of crystallization processes is the use of open-loop simulations with the PBM to train machine-learning control algorithms, such as in the study by Zheng et al 28 They demonstrated how a recurrent neural network (RNN) model trained using a semiempirical PBM could improve the computational efficiency of MPC to achieve an optimal target product yield and crystal size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Szilaǵyi and Nagy 25 showed how parallel GPUs running a high-resolution finite volume technique improved calculation speed significantly, enough for real-time resolution of a multidimensional PBM. Camacho Corzo et al 26 used computational fluid dynamics (CFD) to investigate the hydrodynamics inside a batch crystallizer, suggesting that these simulations could be paired with a morphological PBM to create a more robust representation of the process. 27 Another recent advancement for MPC of crystallization processes is the use of open-loop simulations with the PBM to train machine-learning control algorithms, such as in the study by Zheng et al 28 They demonstrated how a recurrent neural network (RNN) model trained using a semiempirical PBM could improve the computational efficiency of MPC to achieve an optimal target product yield and crystal size.…”
Section: Introductionmentioning
confidence: 99%
“…Szilágyi and Nagy showed how parallel GPUs running a high-resolution finite volume technique improved calculation speed significantly, enough for real-time resolution of a multidimensional PBM. Camacho Corzo et al used computational fluid dynamics (CFD) to investigate the hydrodynamics inside a batch crystallizer, suggesting that these simulations could be paired with a morphological PBM to create a more robust representation of the process …”
Section: Introductionmentioning
confidence: 99%
“…First, such in situ probe-based measurements are point-based methods where the local environment at which the measurements are made may not be representative of the entire crystallization volume. Second, the FBRM-based chord length distributions (CLDs), which are indirect CSD measurements, require sophisticated conversion matrices for nonspherical crystals. , The growth kinetics obtained, obscured by secondary nucleation, is dependent on scale and process parameters (i.e., impeller and tank geometry) due to the spatially inhomogeneous hydrodynamic fields within the crystallizer, resulting in local variation in concentration and mixing rates. Such inherent scale-dependency can cause significant differences between lab, pilot, and industrial manufacturing scales. Furthermore, the growth kinetics data obtained are average values obtained from crystals in constant motion and therefore do not shed detailed quantitative insights into crystal growth phenomena such as the presence of size-dependent growth. , …”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is important to identify critical process parameters (CPPs) appropriately and to control them sufficiently in the manufacturing process. Therefore, much research has been conducted on the crystal habit, particle size, and polymorphism of APIs. …”
Section: Introductionmentioning
confidence: 99%